TEACHING READING NARRATIVE TEXT USING THINK PAIR SHARE (TPS) TECHNIQUE IN CLASS VIII SMPN 03 CIMAHI - Yuniarti, Witri; Yulianti, Yulianti; Syathroh, Isry Laila (IKIP Siliwangi, 2020)
Reading is something important and necessary for students because the achievement of their study depends on the greater part of their ability to read. The aims of the researchers is to investigate the application of Think Pair Share (TPS) technique to improve students reading comprehension. The population were 140 students of class VIII in SMPN 03 Cimahi. The researchers used quantitative method. The instrument that the researchers used are observation, field note, pretest and posttest. The result of this study proved that the Think Pair Share (TPS) technique is effective to be used in learning reading narrative text. The result showed that statistic calculation the mean scores of pretest is 63.43 and the mean scores of posttest is 83.57. So it can be concluded that after students learned reading narrative text using Think Pair Share (TPS) technique, their reading abilities are improved.